PENGARUH DISIPLIN, PENDIDIKAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI SUPERMARKET PAMELLA SATU KOTA YOGYAKARTA - Vernita Meilina Putri Herawati (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2015)
This research have purpose to a) know effect discipline toward employees performance, b) know effect education toward employees performance, c) know effect work environment toward employees performance, d) know effect discipline, education, and work environment in simultaneous toward Supermarket Pamella Satu’s employees performance. Analysis method is simple linear regression analysis. Result of research represent that discipline, education, work environment are not effect toward Pamella Satu Supermarket’s employees performance in partially and simultaneous. That’s can see from Adjusted R2 value, three independent variables give little contributions (4,1%) toward employees performance so 95,9% from other factors. Keywords: discipline, education, work environment